Respuesta :

For this case we have that by definition of vertical translations of functions, it is fulfilled:

Assume [tex]k> 0[/tex]:

To graph [tex]y = f (x) + k[/tex], the graph k units is moved up.

To graph [tex]y = f (x) -k[/tex], the graph moves k units down.

In the figure it is observed that:

The original function is [tex]G (x) = x ^ 2[/tex], the function was moved 4 units down. So, the new function is:

[tex]F (x) = x ^ 2-4[/tex]

Answer:

Option B

Answer:

Option B is correct.

Step-by-step explanation:

G(x) = x^2

then f(x) = x^2-4

since the graph is shifted 4 units down because when something is subtracted from the function the graph is shifted down.

that's why f(x) = x^2-4.

Hence Option B is correct.